2015
DOI: 10.1007/s40653-015-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Behavioral Problems and Trauma Symptoms Among At-Risk Adopted Children Following Trauma-Informed Parent Training Intervention

Abstract: Children who have experienced early adversities are at risk for behavioral problems and trauma symptoms. Using a two-group, pre-post intervention design, the current study evaluated the effectiveness of a parent training utilizing Trust-Based Relational Intervention, a trauma-informed, attachment-based intervention, in reducing behavioral problems and trauma symptoms in at-risk adopted children. Children of parents in the treatment group (n = 48) demonstrated significant decreases in behavioral problems on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 53 publications
2
42
0
1
Order By: Relevance
“…Similarly, the length of time in the adoptive placement varied across studies. The mean length of time in adoptive placement ranged from 12 to 65 months across six studies (Colonnesi et al, 2013;Henderson & Sargent, 2005;Purvis et al, 2015;Razuri et al, 2016;Rushton et al, 2010;Selwyn et al, 2009). One study controlled for length of time in adoptive placement (Colonnesi et al, 2013).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the length of time in the adoptive placement varied across studies. The mean length of time in adoptive placement ranged from 12 to 65 months across six studies (Colonnesi et al, 2013;Henderson & Sargent, 2005;Purvis et al, 2015;Razuri et al, 2016;Rushton et al, 2010;Selwyn et al, 2009). One study controlled for length of time in adoptive placement (Colonnesi et al, 2013).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…One study controlled for length of time in adoptive placement (Colonnesi et al, 2013). Ten studies reported the type of adoption, foster-care (Benjamin, 2010), international (Colonnesi et al, 2013;, or a mixed sample of international, domestic or foster-care adoptions (Baker, 2012;Carnes-Holt, 2010;Opiola, 2016;Purvis et al, 2015;Razuri et al, 2016;Weir et al, 2013;Wydra, 2013).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an ongoing debate whether the current diagnostic criteria for Post Traumatic Stress Disorder (PTSD) are appropriate for all children because it does not distinguish between acute trauma (exposure to a single overwhelming event) and chronic or multiple traumas such as neglect of care and maltreatment over years [7]. Additionally, traditional diagnostic categories such as PTSD are argued to be limited since exposure to traumatic stress in early life is associated with enduring symptoms that not only are incorporate, but also extend beyond PTSD.…”
Section: Introductionmentioning
confidence: 99%